The Effect of Initial Moisture Content, Packaging and Storage Period on Succinate Dehydrogenase and Cytochrome Oxidase Activity of Soybean Seed - Aurellia Tatipata (BIOTROPIA, 2010)
The quality of soybean seed is easily decreased, so that it is difficult to keep them for a long time. The research aims to study the effect of initial moisture content, packaging material and storage period on succinate dehydrogenase and cytochrome oxidase activity. The experimental design was arranged in Factorial in RCB consisting of 3 factors: moisture content, i.e. 8. 10 and 12 percent, packaging materials, i.e. polyethylene, wheat and aluminium foil; storage period i.e. 0, 1, 2, 3, 4, 5, and 6 months. Changes in seed water content, specific activity of succinate and cytochrome oxidase, respiration rate, germination coefficient velocity germination, and abnormal seedlings were monthly determined. It was found that seed moisture content was increase and showed positive correlation with seed moisture content and abnormal seedlings and showed negative correlation with specific activity of succinate dehydrogenase and cytochrome oxidase, respiratory rate, germination and coefficient velocity germination. From this experiment, soybean seeds were stored in polyethylene and aluminium foil bags observed highly succinate dehydrogenase and cytochrome oxidase specific activity, respiration rate, germination, coefficient velocity germination and keep moisture content in low level could delay seed deterioration followed by polyethylene and wheat bags.Â  Key words: moisture content, succinate dehydrogenase, cytochrome oxidase, soybean